DISCUSSION OF THE CHALLENGES FACED BY ECONOMICS STUDENTS IN ACQUIRING LANGUAGE PROFICIENCY FOR EFFECTIVE COMMUNICATION (Лучшие интеллектуальные исследования, 2025)
Abstract: Effective communication is crucial for success in the field of economics. This article discusses the challenges faced by economics students in acquiring the necessary language proficiency for effective communication, particularly in academic and professional settings. It explores the specific linguistic demands of economics, the impact of language proficiency on academic performance and career prospects, and potential strategies for addressing these challenges. The article draws upon existing literature to illustrate the complexities of language acquisition in this specialized domain.